Competition or exhibition? The Olympic arts and cultural policy rhetoric. Issue 2 (4th March 2018) - Ingraham, Chris
Abstract : Though they are widely forgotten today, the modern Olympic Games once offered competitive medals for art. This tradition, which lasted through the seven summer Games held from 1912 to 1948, found artists competing for gold much as athletes do now. These artists represented their nation in judged competitive events showcasing artistic works. In its initial form, the 'pentathlon of the muses, ' as it was called, included competitive events in Architecture, Musical Composition, Sculpture, Painting, and Literature. This paper considers the history of these arts competitions and their eventual demise as a study in cultural policy, arguing that no understanding of cultural policy is sufficient unless it considers the rhetorical factors that contribute to its formation. Without abandoning the Foucauldian backbone of cultural-policy studies, this argument makes an interdisciplinary plea to open cultural policy studies to the field of rhetorical scholarship, which it has almost wholly neglected to date.